The Prevalence of the Classical and Non-Classical Cardiovascular Risk Factors in Multiple Sclerosis Patients - Sternberg, Zohara; Leung, Christopher; Sternberg, Daniel; Li, Fan; Karmon, Yuval; Chadha, Kailash; Levy, Elad (CNS & Neurological Disorders - Drug Targets, 2013)
Background: Inflammation is known to play a role in cererovascular risk. Multiple sclerosis (MS) is a neurodegenerative disease that is initially characterized by inflammatory changes in the brain. We hypothesized that due to chronic inflammation, MS patients would present with a higher levels of cardiovascular (CV) risk factors than non-MS patients. Methods: We performed a retrospective chart review on 206 MS patients and 142 control patients suffering from meningiomas and acoustic neuromas, non inflammatory, non autoimmune diseases of the brain. The obtained data included fasting lipid profiles, plasma glucose, systolic and diastolic blood pressure (BP), serum levels of homocysteine and uric acid, data on iron status, smoking habit, and list of medications. In addition, data on indicators of MS disease severity was obtained for MS patients. Results: MS patients had significantly higher total plasma cholesterol, p = 0.01, and plasma high density lipoprotein, P <0.001, but lower plasma glucose, P <0.001, and systolic BP, P = 0.001, than non-MS patients. In addition, MS patients had lower erythrocyte sedimentation rate and serum vitamin B12, but higher serum folic acid and vitamin D3 than non-MS patients. A positive correlation was observed between plasma glucose and the extended disability status scale (EDSS), P = 0.008, and between plasma glucose and the rate of clinical relapse, P = 0.001. Conclusion: The MS pathophysiology may be among factors for the lower CV risk factors in MS patients. Future studies should examine whether the chronic use of many pharmacological agents influence CV risk factors in MS patients.
Keywords: multiple sclerosis